PCR-based detection of Botryosphaeria canker pathogens in fig trees - Mahdiyeh Ghaedi; Zeinab Bolboli; Hamed Negahban; Reza Mostowfizadeh-Ghalamfarsa (Scientific Reports)
Abstract Canker and dieback, caused by members of the Botryosphaeriaceae family, pose significant threats to plant productivity, food security, and natural ecosystems, particularly in economically important woody crops including fig trees. Detecting and identifying these pathogens is challenging due to their latent infections and the presence of multiple pathogens within the same host. In our study, we developed a PCR assay using three carefully selected primer pairs based on sequence differences in two protein-coding genes, β-tubulin and RNA polymerase II. The species-specific primers TUB-Bd1 (specific for Botryosphaeria dothidea), TUB-Np1 (specific for Neofusicoccum parvum), and RPB-Nd2 (specific for Neoscytalidium dimidiatum) effectively amplified target gene sequences in pure cultures and infected tissue samples using PCR and nested PCR conditions. The efficiency test results demonstrated that TUB-Bd1, TUB-Np1, and RPB-Nd2 primer pairs could detect specific DNA fragments at very low concentrations in nested PCR. Furthermore, we collected 180 symptomatic and asymptomatic fig samples from different regions of Fars Province, Iran. Applying the species-specific primer pair RPB-Nd2 in direct PCR led to the detection of N. dimidiatum in 25.5% of symptomatic woody samples and 13% of asymptomatic one-year-old branch samples of fig trees. This represents a significant improvement compared to the mere 6.67% detected using traditional culturing methods on PDA. Interestingly, neither B. dothidea nor N. parvum were detected in the 180 samples using nested PCR. Moreover, multiplex PCR enabled simultaneous DNA detection of the target Botryosphaeriaceae pathogens. Our findings emphasize the importance of molecular techniques for early detection of evident and latent infections caused by these three pathogens in fig trees.